Characterization of Agronomic and Seed Oil Features for Different Cultivars of Tree Peony - Hao Wang; Shuo Wei; Yinglong He; Xiaohui Wang; Yuying Li; Dongfeng Wei; Zhanying Wang; Lili Guo; Muhammad Shaaban; Xiaogai Hou (Plants, 2023)
Tree peony is a unique oil plant resource in China, and tree peony seed oil is one of the healthy edible oils with a very promising future. However, the main oil tree peony cultivars promoted in China are Paeonia ostii ‘Fengdan’ and Paeonia rockii. In order to explore new oil tree peony cultivars, 68 tree peony cultivars were investigated and cultivars with oil potential were selected by cluster analysis and grey relational analysis (GRA) in this study. The results demonstrated that the 68 cultivars varied significantly in terms of agronomic characteristics (p < 0.05), with the coefficient of variation in seed yield per plant reaching a high of 75.36%. The oil content of 46 cultivars was higher than ‘Fengdan’ (20.87 ± 0.26%) and ‘Zibanbai’ (21.24 ± 1.01%), while the alpha-linolenic acids and total unsaturated fatty acid contents of 26 cultivars were higher than ‘Fengdan’ (39.79 ± 1.13% and 88.99 ± 0.47%) and ‘Zibanbai’ (40.51 ± 0.09% and 93.59 ± 0.09%). Finally, three cultivars with better integrated traits were selected by cluster analysis and grey relational analysis (GRA), comprising of ‘Changshoule’, ‘Xianchizhenghui’, and ‘Yupantuojin’. The contents of alpha-linolenic acids and total unsaturated fatty acids in ‘Changshoule’ (47.98 ± 0.17% and 93.60 ± 0.08%), ‘Xianchizhenghui’ (49.44 ± 0.63% and 93.80 ± 0.06%), and ‘Yupantuojin’ (40.46 ± 0.26% and 93.58 ± 0.06%) were higher than that of ‘Fengdan’ (39.79 ± 1.13% and 88.99 ± 0.47%). In general, these cultivars can be used as hybrid parental materials for breeding new excellent oil tree peony cultivars.